Multimedia Integration in Learning to Draw Women's Body Proportions: A Case Study of Class X Fashion Students at SMK Darussalam Banyuwangi - Muimamah, Rosita Relvina Putri; Marniati, Marniati; Rahayu, Imami Arum; Yuniati, Mita (PT. Riset Press International, 2024)
This study aims to apply integrated multimedia learning in drawing female body proportions to enhance student learning outcomes. This research is a form of classroom action research (PTK). The subjects of this study were class X students of Fashion Design SMK Darussalam Banyuwangi totaling 25 students. Data collection techniques use observation, questionnaires, and cognitive and psychomotor tests. Learning outcomes using Video Tutorials, Handouts, and LKPD showed an average score in cycle I of 3.5 and cycle II of 3.8, with good categories. Student responses to learning media received an assessment of 91%, which was categorized as good. The level of student engagement in the use of this media reached 91%, indicating excellent engagement. Student learning outcomes experience significant improvements in each cycle. The average affective completeness increased from 3.6 in cycle I to 3.8 in cycle II. Post-test cognitive completeness also rose from 81% in cycle I to 97% in cycle II. Overall post-test completeness increased from 78% in cycle I to 91% in cycle II. The application of Video Tutorials, Handouts, and LKPD media has proven effective in improving student learning outcomes, with excellent levels of engagement and learning outcomes. This research was stopped in cycle II because it had reached the Learning Objectives Attainment Criteria (KKTP).